2008
DOI: 10.1093/nar/gkn370
|View full text |Cite
|
Sign up to set email alerts
|

Real-time detection of Fe{middle dot}EDTA/H2O2-induced DNA cleavage by linear dichroism

Abstract: The conditions for the measurement of linear dichroism (LD) can be adjusted so as to solely reflect the length and the flexibility of DNA. The real-time detection of the EDTA·Fe2+-induced oxidative cleavage of double-stranded native and synthetic DNAs was performed using LD. The decrease in the magnitude of the LD at 260 nm, which reflects an increase in the flexibility and a decrease in the length of the DNA, can be described by the sum of two or three exponential curves in relation to the EDTA·Fe2+ concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Linear dichroism (LD) is defined by the difference in the absorption of polarized parallel and perpendicular radiation relative to the laboratory reference axis of the oriented sample [39][40][41]. The use of LD as a tool for detecting dsDNA cleavage in real-time is described elsewhere [19,[33][34][35]39].…”
Section: Ld and Other Spectroscopic Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Linear dichroism (LD) is defined by the difference in the absorption of polarized parallel and perpendicular radiation relative to the laboratory reference axis of the oriented sample [39][40][41]. The use of LD as a tool for detecting dsDNA cleavage in real-time is described elsewhere [19,[33][34][35]39].…”
Section: Ld and Other Spectroscopic Measurementsmentioning
confidence: 99%
“…The use of LD as a tool for detecting dsDNA cleavage in real-time is described elsewhere [19,[33][34][35]39]. The electrochemical measurements were conducted using an Ag/AgCl reference electrode, coiled platinum counter electrode and glassy carbon electrode (Bioanalytical Systems Inc., A = 0.071 cm 2 ).…”
Section: Ld and Other Spectroscopic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43][44] Here, we report the synthesis and characterization of various transition metal complexes containing a dipyridylamine-based ligand bearing the anthracene moiety (Fig. [41][42][43][44] Here, we report the synthesis and characterization of various transition metal complexes containing a dipyridylamine-based ligand bearing the anthracene moiety (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44] Here, we report the synthesis and characterization of various transition metal complexes containing a dipyridylamine-based ligand bearing the anthracene moiety (Fig. The experimental results showed that they can induce considerable oxidative DNA cleavage in the presence hydrogen peroxide and dioxygen.…”
mentioning
confidence: 99%